Biological characteristics of human menstrual blood‐derived endometrial stem cells. Issue 3 (26th December 2017) - Liu, Yanli; Niu, Rongcheng; Yang, Fen; Yan, Yan; Liang, Shengying; Sun, Yuliang; Shen, Ping; Lin, Juntang
Abstract: Successful isolation of human endometrial stem cells from menstrual blood, namely menstrual blood‐derived endometrial stem cells (MenSCs), has provided enticing alternative seed cells for stem cell‐based therapy. MenSCs are enriched in the self‐regenerative tissue, endometrium, which shed along the periodic menstrual blood and thus their acquisition involves no physical invasiveness. However, the impact of the storage duration of menstrual blood prior to stem cell isolation, the age of the donor, the number of passages on the self‐renewing of MenSCs, the paracrine production of biological factors in MenSCs and expression of adhesion molecules on MenSCs remain elusive. In this study, we confirmed that MenSCs reside in shedding endometrium, and documented that up to 3 days of storage at 4°C has little impact on MenSCs, while the age of the donor and the number of passages are negatively associated with proliferation capacity of MenSCs. Moreover, we found that MenSCs were actually immune‐privileged and projected no risk of tumour formation. Also, we documented a lung‐ and liver‐dominated, spleen‐ and kidney‐involved organic distribution profile of MenSC 3 days after intravenous transfer into mice. At last, we suggested that MenSCs may have potentially therapeutic effects on diseases through paracrine effect and immunomodulation.